Effect of Restricted Feeding on Metabolic Health and Sleep-Wake Rhythms in Aging Mice - Xu, Yong-Xia; Liu, Guo-Ying; Jiang, Qian; Bi, Han-Qi; Wang, Shi-Chan; Zhang, Ping-Ping; Gao, Chao-Bing; Chen, Gui-Hai; Cheng, Wen-Hui; Chen, Guan-Jun; Zhu, De-Fa; Zhong, Ming-Kui; et al. (Frontiers in Neuroscience, 2021)
Aging, an irreversible and unavoidable physiological process in all organisms, is often accompanied by obesity, diabetes, cardiovascular diseases, sleep disorders, and fatigue. Thus, older adults are more likely to experience metabolic symptoms and sleep disturbances than are younger adults. Restricted feeding (RF) is a dietary regimen aimed at improving metabolic health and extending longevity, as well as reorganizing sleep-wake cycles. However, the potential of RF to improve metabolic health and sleep quality in older adults who are known to show a tendency toward increased weight gain and decreased sleep is unknown. To elucidate this issue, aged mice were assigned to an RF protocol during the active phase for 2 h per day for 2 weeks. Sleep-wake cycles were recorded during the RF regime in RF group and control mice. At the end of this period, body weight and blood biochemistry profiles, including blood glucose, cholesterol, and enzyme activity, in addition to dopamine concentrations in the brain, were measured in the RF group and age-matched controls. RF for 2 weeks improved the metabolic health of aged mice by reducing their body weights and blood glucose and cholesterol levels. At the beginning of the RF regime, sleep decreased in the dark period but not in the light period. After stable food entrainment was achieved (7 days post-RF commencement), the amount of time spent in wakefulness during the light period dramatically increased for 2 h before food availability, thereby increasing the mean duration of awake episodes and decreasing the number of wakefulness episodes. There was no significant difference in the sleep-wake time during the dark period in the RF group, with similar total amounts of wakefulness and sleep in a 24-h period to those of the controls. During the RF regime, dopamine levels in the midbrain increased in the RF group, pointing to its potential as the mechanism mediating metabolic symptoms and sleep-wake regulation during RF. In conclusion, our study suggested that RF during aging might prohibit or delay the onset of age-related diseases by improving metabolic health, without having a severe deleterious effect on sleep.